Strategi Kreatif Program Totwit di Radio RDI 97.1 FM - Yunita; Agustrijanto (UNIVERSITAS KALBIS, 2022)
Strategy is one of the ways that radio stations use to attract their listeners with the aim of advancing the radio station.The creative strategy used by Totwit program is to provide interesting content with betawi and batak accents as a characteristic of RDI radio.The purpose of this research is to see the creative strategies created by the Totwit program in producing broadcast programs on RDI radio.This research uses the paradigm of Constructivism with a descriptive qualitative research approach.The methods used in this study are observations, in-depth interviews, documentation and case studies.This research uses peter pringle concept which consists of program planning, program production, program execution and program supervision.The results of this study show that Radio RDI in the Totwit program has a strategy to create a program so that many listeners with the characteristics of betawi and batak language and establish good relationships with listeners.